The Effect of Intellectual Capital On Company’s Performance Study on Manufacturing Companies Listed on The Indonesia Stock Exchange (IDX) - Rinanda, Najati (Riau International Conference on Economics, Business and Accounting, 2025)
This study aims to determine (1) the effect of aggregate intellectual capital (VAIC) on the performance of companies that have unequal intellectual capital intensity. (2) To examine the effect of intellectual capital components (VACA, VAHU, and STVA) individually and simultaneously on the performance of companies that have unequal intellectual capital intensity as well. Intellectual capital is measured by the Value Added Intellectual Capital (VAIC) method and company performance is measured by financial performance (return on assets) and market valuation (market to book value). This study uses manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022 as samples. Data was collected using purposive sampling method with 30 observation data analyzed. This analysis uses a panel regression model (with dummy) as the primary analytical tool. The results of this study prove that there is a significant difference between the intellectual capital of manufacturing companies in high capital intensive industries and low capital intensive industries. ROA in high IC intensive industrial companies is better than ROA in low IC intensive industrial companies; positive and significant effect because the probability value is less than 0.1. MBV in low IC intensive industrial companies is better than MBV in high IC intensive industrial companies; positive and significant effect because the probability value is less than 0.1. Then, intellectual capital and dummy simultaneously have a significant effect on financial performance and market valuation.